Implementasi Algoritma C4.5 pada Analisis Faktor Risiko Penyakit Jantung Koroner - Yestina, Elsa Adinda; Prakoso, Bakhtiyar Hadi; Selviyanti, Erna; Suyoso, Gandu Eko Julianto (Universitas Budi Darma, 2025)
Coronary heart disease is a non-communicable disease due to the process of atherosclerosis resulting in blockage or narrowing of the coronary blood vessels which causes reduced oxygen supply to the heart. In the morbidity and mortality data at RSD dr. Soebandi Jember from 2020-2024, there were fluctuations. In terms of age, the majority of sufferers are productive aged between 15-64 years. The impact that has occurred is an increade in cases of coronary heart disease which is getting higher and decreasing productivity at a productive age. The purpose of this studywas to analyze risk factors for coronary heart disease based on medical records of inpatients using the C4.5 algorithm at RSD dr. Soebandi Jember. This research uses the C4.5 algorithm method with RapidMiner tools and impelents k-fold cross validation. The selection of the C4.5 algorithm is because is produces classification basen on the gain ratio value so that the classification results can be analyzed for risk factor attributes. Determination of risk factors is known in the decision results in the form of classification rules. The implementation k-fold cross validation produces the highest accuracy at k=8, namely accuracy of 86,09%, precision of 82,63%, and recall of 91,39%. Based on the results, diabetes mellitus is the most influential risk factor for coronary heart disease because it has the highest gain ratio value. Other risk factors are physical inactivity, gender, obesity, hugh blood pressure, age, and smoking. Suggestions for dr. Soebandi Hospital are to improve Communication, Information, Education (IEC), especially for diabetes mellitus patients because it affects coronary heart disease.